Zooplankton Diversity and their Monthly Variation Reflecting Cultural Eutrophication of Chakki Talab, Bodhan, Telangana, India - Lingampally Vasudha; Solanki V.R.; S. Sabita Raja (Contemporary Research and Perspectives in Biological Science Vol. 3, 2024)
The present work aimed to determine the monthly variations of zooplankton, the potent biological indicators to know the ecological status of Chakki Talab, Bodhan, India. Multiple studies have made a consistent and crucial realization that zooplankton taxa are rapid responders to many environmental stressors, such as hydrological changes, climate changes and anthropogenic activity-induced water pollution. Chakki Talab, located in Bodhan, Telangana, India, is one of the urban lakes in the country facing challenges from excessive nutrient input, which contributes to cultural eutrophication and subsequently degrades water quality. In freshwater bodies, zooplankton play an important role in maintaining the ecological balance and are used as potential bioindicators for assessing water quality, biological monitoring and changing trophic conditions. In the study conducted over a year, from October 2015 to September 2016, the zooplankton diversity of Chakki Talab was assessed on a monthly basis. The relative abundance of zooplankton was observed to be highest with Rotifera (31%), followed by Ostracoda (27%), Protozoa (21%), Copepoda (11%), Chironomidae (9%), and Cladocera (1%). The predominance of Rotifera, throughout the investigation indicates a significant influx of nutrients into Chakki Talab from nonpoint sources. To mitigate the impact of nutrient overloading and to preserve the ecological status of Chakki Talab, it is advisable to implement ongoing monitoring and management strategies. Continuous surveillance is crucial to track changes in water quality and to ensure the sustainability of this freshwater ecosystem.